Charting the solar cycle - Chapman, S. C. (Frontiers in Astronomy and Space Sciences, 2023)
Sunspot records reveal that whilst the sun has an approximately 11 year cycle of activity, no two cycles are of the same duration. Since this activity is a direct driver of space weather at earth, this presents an operational challenge to quantifying space weather risk. We recently showed that the Hilbert transform of the sunspot record can be used to map the variable cycle length onto a regular 'clock' where each cycle has the same duration in Hilbert analytic phase. Extreme geomagnetic storms rarely occur within the quiet part of the cycle which is a fixed interval of analytic phase on the clock; there is a clear active-quiet switch-off and quiet-active switch-on of activity. Here we show how the times of the switch-on/off can be determined directly from the sunspot time-series, without requiring a Hilbert transform. We propose a method- charting- that can be used to combine observations, and reports of societal impacts, to improve our understanding of space weather risk.